Quality Evaluation of Transparent Soap from Whey Waste with Butterfly Pea Flower Extract (Clitoria ternatea L.) - Eva Malahayati; Dian Puspita Anggraini; Latifatul Nararia Kusuma (Indonesian Journal of Biology Education, 2023)
The attractive appearance of soap and its various benefits make it the choice of consumers. Transparent solid soap had a transparent appearance, so it was more attractive and produced softer foam than other soaps. This research aimed to create a good combination by utilizing tofu whey waste as a transparent soap ingredient with butterfly pea flower extract (Clitoria ternatea L.) to produce environmentally friendly soap. Utilization of tofu whey waste as an alternative to sucrose and butterfly pea flower extract as the active substance triclosan from natural ingredients that contain antibacterials and antioxidants. The results of this research showed that the addition of butterfly pea flower extract produces a yellowish-white soap preparation, with a dense texture, not transparent, and a distinctive slightly sweet soap aroma. The characteristics of soap preparations from whey waste with the addition of butterfly pea flower extract had a pH of 10.7, foam stability of 70%, water content of 29%, and did not irritate.